2006
DOI: 10.1108/10867370610683914
|View full text |Cite
|
Sign up to set email alerts
|

Technical analysis and the stochastic properties of the Jordanian stock market index return

Abstract: This paper investigates the performance of moving average rule in an emerging market context, namely that of the Jordanian stock market. The returns from trading strategies based on various moving average rules are examined. The results show that technical trading rules can help to predict market movements, and that there is some evidence that (short) rules may be profitable after allowing for transactions costs, although there are some caveats on this. Sensitivity analysis of the impact of transaction costs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 47 publications
0
4
0
1
Order By: Relevance
“…The study reported strong positive relationship between turnover and past returns. Atmeh and Dobbs (2006) investigated the performance of moving average trading rules in the Jordanian stock market and found that technical trading rules can help to predict market movements. Moreover, Al-Khouri and Ajlouni 2007reported that the price-limit technique was effective in reducing the volatility in the Amman stock exchange.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The study reported strong positive relationship between turnover and past returns. Atmeh and Dobbs (2006) investigated the performance of moving average trading rules in the Jordanian stock market and found that technical trading rules can help to predict market movements. Moreover, Al-Khouri and Ajlouni 2007reported that the price-limit technique was effective in reducing the volatility in the Amman stock exchange.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Furthermore, Atmeh and Dobbs (2006) Patel et al (2015) compared four prediction models to forecast the trend direction in the Indian financial markets: random forest, Support Vector Machine (SVM), Artificial Neural Network (ANN), and Naive-Bayes. The results recommended that random forest beats the three other expectation models on overall performance.…”
Section: Studies Conducted In the Emerging Marketsmentioning
confidence: 99%
“…Al-Khouri and Ajlouni 30 reported that the price-limit technique was effective in reducing the volatility in the Amman stock exchange. Al Janab 31 33 investigated the performance of moving average trading rules in the Jordanian stock market and found that technical trading rules can help predict market movements. Hassan and Yu 34 reported that in spite of the recent extreme fluctuations of the MENA stock markets, there was no strong evidence of rational speculative bubbles of either domestic or US-based investors.…”
Section: Review Of the Related Literaturementioning
confidence: 99%